2022
DOI: 10.1140/epjc/s10052-021-09981-1
|View full text |Cite
|
Sign up to set email alerts
|

GW200105 and GW200115 are compatible with a scenario of primordial black hole binary coalescences

Abstract: Two gravitational wave events, i.e. GW200105 and GW200115, were observed by the Advanced LIGO and Virgo detectors recently. In this work, we show that they can be explained by a scenario of primordial black hole binaries that are formed in the early Universe. The merger rate predicted by such a scenario could be consistent with the one estimated from LIGO and Virgo, even if primordial black holes constitute a fraction of cold dark matter. The required abundance of primordial black holes is compatible with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The precision in this field is increasingly becoming a possible discriminator between the plethora of models in modified gravity. In addition to precise observations of the final phases of the coalescence of binary BHs [19], neutron stars [20], and other scenarios [21,22], we also have confirmed observations from multimessenger astronomy [20,23] and direct observations of the shadow of a supermassive BH [24]. This process is set to drastically increase with the next generation of gravitational wave observatories such as LIGO India [25], the Einstein Telescope [26] and LISA [27], among others, which will drastically increase the number of event observations enlarging the possibility of observing more exotic phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…The precision in this field is increasingly becoming a possible discriminator between the plethora of models in modified gravity. In addition to precise observations of the final phases of the coalescence of binary BHs [19], neutron stars [20], and other scenarios [21,22], we also have confirmed observations from multimessenger astronomy [20,23] and direct observations of the shadow of a supermassive BH [24]. This process is set to drastically increase with the next generation of gravitational wave observatories such as LIGO India [25], the Einstein Telescope [26] and LISA [27], among others, which will drastically increase the number of event observations enlarging the possibility of observing more exotic phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the BH-BH and NS-NS mergers, BH-NS events constitute another major class of mergers and carry significant implications for multimessenger observations (Ruiz et al 2021). While the detected events are consistent with stellar evolution formation channels (Broekgaarden & Berger 2021), speculations about possible PBH origin, considering that NSs are misidentified solar-mass BHs and detected events correspond to unequal mass PBH-PBH mergers, have already been put forth (Wang & Zhao 2022). As the number of detected events will significantly accumulate in the upcoming future and given their possible implications for fundamental physics, understanding their origin is a pressing matter.…”
Section: Introductionmentioning
confidence: 86%
“…After the announcement of Abbott et al (2021), various works on the population of these binaries have appeared. Wang & Zhao (2022) explained these GW events in a scenario of primordial BH (PBH) binaries (not NS-BHs) that satisfies existing astrophysical/cosmological bounds (see also Chen et al (2021) for another study on a PBH scenario). Sasaki et al (2021) showed that the NS-PBH merger rate is subdominant to the NS-BH rate.…”
Section: Introductionmentioning
confidence: 89%